2013
DOI: 10.1007/s00167-013-2539-3
|View full text |Cite
|
Sign up to set email alerts
|

Arthrodesis of the knee following failed arthroplasty

Abstract: There is no definite answer as to which method is superior in performing an arthrodesis of the knee. Intramedullary nailing achieved the best fusion rates, but was used most in cases without--or cured--infection. Our data and the contemporary literature suggest that external fixation can be abandoned as standard fusion method, but can be of use following persisting infection. The Ilizarov circular external fixator, however, seems to render high fusion rates. Good patient selection and appropriate individual tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
39
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 44 publications
(45 citation statements)
references
References 35 publications
(92 reference statements)
3
39
0
3
Order By: Relevance
“…In regards to patients who present with severe bony defects, IM nailing serves as a reliable treatment option. As evidenced in a recent study by Van Rensch et al assessing the effects that the severity of bony defects has on arthrodesis outcomes, IM nailing showed comparable fusion rates (compared to previously published series) despite the majority of patients presenting with type III bony defects (according to the Anderson classification) [8] . Different variations of treatment have been proposed to overcome extensive bone loss including the possibility of lengthening the bone using a circular frame, the use of bone grafts with IM nails, or newer modular IM nail techniques that do not require bone-to-bone contact [1,9,10] .…”
Section: Indications For Each Techniquementioning
confidence: 62%
See 4 more Smart Citations
“…In regards to patients who present with severe bony defects, IM nailing serves as a reliable treatment option. As evidenced in a recent study by Van Rensch et al assessing the effects that the severity of bony defects has on arthrodesis outcomes, IM nailing showed comparable fusion rates (compared to previously published series) despite the majority of patients presenting with type III bony defects (according to the Anderson classification) [8] . Different variations of treatment have been proposed to overcome extensive bone loss including the possibility of lengthening the bone using a circular frame, the use of bone grafts with IM nails, or newer modular IM nail techniques that do not require bone-to-bone contact [1,9,10] .…”
Section: Indications For Each Techniquementioning
confidence: 62%
“…Parcel observed that in patients with type III AORI classified bony deficiency in both the femoral and tibial aspects, lower fusion rates occurred when treated with modular nails [16] . Similarly, Van Rensch reported a decrease in fusion rates among multiple techniques of arthrodesis when there was only ¾ -¼ femorotibial surface contact immediately following arthrodesis versus surface contact of greater than ¾ [8] .…”
Section: Indications For Specific Knee Arthrodesis Techniquementioning
confidence: 95%
See 3 more Smart Citations